Comparison of physicochemical properties and aqueous solubility of xanthone prepared via oil-in-water emulsion and complex coacervation techniques. Issue 1 (1st January 2018) - Ho, Li Yoke; Lim, Yau Yan; Tan, Chin Ping; Siow, Lee Fong
ABSTRACT: The aim of this study was to enhance aqueous solubility of xanthone with natural polymers using oil-in-water emulsion and complex coacervation as the microencapsulation techniques. There was no interaction between xanthone and the wall material; and xanthone crystallinity was decreased as observed via fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and x-ray powder diffraction (XRD) after microencapsulation. Oil-in-water emulsion and coacervation increased xanthone solubility by 37-fold and 1.6-fold, respectively. However, O/W emulsion method required a high ratio of oil to xanthone. The solubilizing effect of oil and wall material, particle size reduction, and decreased crystallinity were responsible for enhancing the aqueous solubility of xanthone.